Competitiveness of international new ventures in Uganda - Nabatanzi-Muyimba, Annet K. (My University, 2015)
International competitiveness is the ability of a firm to sustain its international performance relative to competitors over time and in the future. This research examined the firm level factors that contribute to competitiveness of international new ventures (INVs). Specifically, the study investigated whether entrepreneurial and branding resources and capabilities greatly contribute to competitiveness of INVs. The study followed a positivist and quantitative methodological approach to establish the causalities and social order of competitiveness of INVs in Uganda. The purpose of the study was actualized through adopting a cross-sectional survey design. The study focused on INVs which are firms that internationalized their operations within the first ten (10) years of their establishment. These firms were drawn from the three major business sectors in Uganda including agribusiness, manufacturing and service firms involved in international activities ranging from exports, input sourcing (imports), foreign subsidiaries, franchises to international subcontracting. The survey instrument was delivered to 405 firms and information required was provided by three different groups of respondents in each firm. Owners-managers and employees assessed their firm’s entrepreneurial and branding resources and capabilities and international competitiveness in the last five (5) years and for the next three (3) years whereas customers evaluated brand advantage of firms and their products or services. The data collection process achieved a 77 percent response rate to the study. The study was non-experimental and adopted structural equation modelling and Average Moments of Structures (AMOS) to establish the causal relationships between the study variables. The study results reveal that brand orientation greatly contributes to international competitiveness whereas the interaction between entrepreneurial and branding resources and capabilities significantly enhances brand advantage of INVs. In addition, the study indicates that in the short run, brand advantage constrains the contribution of entrepreneurial and branding capabilities to competitiveness of INVs. The findings of this research provide knowledge on building and sustaining international competitiveness with specific implications for improving marketing and/or branding capabilities and utilization of entrepreneurial resources. The findings further support the dynamic capabilities theory in explaining competitiveness of INVs in Uganda. Keywords: Competitiveness, Entrepreneurial Capital, Entrepreneurial orientation, Brand orientation, Brand Advantage, International New Ventures, Uganda
Thesis (Ph.D.)--University of the Witwatersrand, Faculty of Commerce, Law and Management, Graduate School of Business Administration, 2014.
Keywords: Competitiveness; Brand advantage; Entrepreneurial orientation; International new ventures; Uganda